(untitled) (Fiep Bulletin - online, 2014)
The research set as a cross-sectional descriptive- analytic in the city of Imperatriz (Maranhão). This study involved a sample of 118 adolescents aged 14-18 years in order to identify the influence of overweight and central obesity levels of flexibility in adolescents . According to the data, body mass index ( BMI) of the sample was 20.84 ( ± 2.96 ) kg/m2 , a waist circumference (WC ) of 72.33 ( ± 8.44 ) and test sit and Reach (TSR) of 33.42 ( ± 10.48 ) cm . Assessing the levels of flexibility , we found that most teenagers fits the classification of " reasonable " 34 ( 28.8 % ) subjects , while 24 ( 20.3% ) subjects in the classification " good " and others 22 ( 18.7% ) in the classification "very weak " , although 19 ( 16.1% ) are in the classification of " weak " and other 19 ( 16.1% ) were classified as " good" . The female subjects divided into levels of waist circumference : fine ( 78.46 % ) , moderately high ( 18.46 % ) , high ( 0.00 % ) and very high ( 3.08 % ), The subjects males according to the levels of waist circumference : fine ( 64.15% ) , moderately high ( 24.53 % ) , high ( 9.43 % ) and very high ( 1.89 % ) . The results of this study suggest that the values ??of waist circumference showed a weak correlation with the flexibility ,ie , high or low values ??in circumference showed no relationship with the flexibility , so this sample , the flexibility of teenagers was not affected by the variation the WC .